MODEL PERUBAHAN PENGGUNAAN LAHAN DAN PENDUGAAN CADANGAN KARBON DI DAERAH ALIRAN SUNGAI CISADANE, JAWA BARATLANDUSE CHANGE MODEL AND CARBON STOCK ESTIMATION IN CISADANE WATERSHED, WEST JAVA - Antonio Alberto; Bambang Dwi Dasanto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2010)
Land use and land cover in Cisadane Watershed are very vulnerable to switch over, which is caused by the high rate of population growth. Land use and land cover change cause the carbon stock changes. These changes were analysed using the logistic regression models, and in this analysis we used land use maps in 2001 and 2006. As many as 44 regression equations were developed with various values of determination coefficient (R2); 14% of the R2 was less than 0.50, 29% was between 0.50 and 0.75, and 57% is than 0.75. Statistically, there were 31 equations suitable to generate landuse map in 2010, 2015, 2020, and 2025. The amount of carbon stocks in Cisadane Watershed until the year 2025 tend to decrease, so the sum of carbon emissions in the atmosphere increased. This was mainly due to conversion of forest area into other landuse types. Land use and land cover in Cisadane Watershed are very vulnerable to switch over, which is caused by the high rate of population growth. Land use and land cover change cause the carbon stock changes. These changes were analysed using the logistic regression models, and in this analysis we used land use maps in 2001 and 2006. As many as 44 regression equations were developed with various values of determination coefficient (R2); 14% of the R2 was less than 0.50, 29% was between 0.50 and 0.75, and 57% is than 0.75. Statistically, there were 31 equations suitable to generate landuse map in 2010, 2015, 2020, and 2025. The amount of carbon stocks in Cisadane Watershed until the year 2025 tend to decrease, so the sum of carbon emissions in the atmosphere increased. This was mainly due to conversion of forest area into other landuse types.